Effect of Trinucleotide Repeats in the Huntington's Gene on Intelligence - Lee, Jessica K. (EBioMedicine, 2018)
BACKGROUND: Huntington's Disease (HD) is caused by an abnormality in the HTT gene. This gene includes trinucleotide repeats ranging from 10 to 35, and when expanded beyond 39, causes HD. We previously reported that CAG repeats in the normal range had a direct and beneficial effect on brain development with higher repeats being associated with higher cognitive function. The current study now expands this line of inquiry to evaluate the effects of CAG repeat throughout the entire spectrum of repeats from 15 to 58. METHODS: We evaluated brain function in children ages 6–18 years old. DNA samples were processed to quantify the number of CAG repeats within HTT. Linear regression was used to determine if number of CAG repeats predicted measures of brain function. FINDINGS: The number of repeats in HTT, had a non-linear effect on a measure of general intelligence with an inverted U shape pattern. Increasing repeat length was associated with higher GAI scores up until roughly 40–41 repeats. After this peak, increasing repeat length was associated with declining GAI scores. INTERPRETATION: HTT may confer an advantage or a disadvantage depending upon the repeat length, playing a key role in the determination of intelligence, or causing a uniquely human brain disease.